1993
DOI: 10.1177/00220345930720020601
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Cathepsin D in Rat Junctional Epithelium

Abstract: Localization of cathepsin D was studied in the junctional epithelium (JE) of healthy rat gingivae by immuno-light and -electron microscopy, by means of both the avidin-biotin-peroxidase complex method and a colloidal gold IgG method. At the light-microscopic level, cathepsin D was demonstrated in the JE and oral sulcular epithelium (OSE). Cathepsin D immunoreactivity was remarkable in the coronal portion of the JE and decreased toward its apical portion. However, cathepsin D immunoreactivity in the basal cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, the formation of this superoxide anion (Tanabe et al 1996) and endocytosis of IgG-opsonized materials by neutrophils (Fallman et al 1989;Lew et al 1985) have been reported to depend on the activation of NK 1 -R/G-protein-linked phosphoinositide turnover and the resulting increase in intracellular Ca 2+ concentrations. Judging from the findings that the JE is densely innervated by SP-immunoreactive nerves and that NK 1 -R was found in the JE cells, the proliferation (Schroeder 1986) and endocytotic ability (Ayasaka et al 1993;Yamaza et al 1997) of JE cells and the migration and endocytotic ability of neutrophils may be modulated by the binding of NK 1 -R with SP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the formation of this superoxide anion (Tanabe et al 1996) and endocytosis of IgG-opsonized materials by neutrophils (Fallman et al 1989;Lew et al 1985) have been reported to depend on the activation of NK 1 -R/G-protein-linked phosphoinositide turnover and the resulting increase in intracellular Ca 2+ concentrations. Judging from the findings that the JE is densely innervated by SP-immunoreactive nerves and that NK 1 -R was found in the JE cells, the proliferation (Schroeder 1986) and endocytotic ability (Ayasaka et al 1993;Yamaza et al 1997) of JE cells and the migration and endocytotic ability of neutrophils may be modulated by the binding of NK 1 -R with SP.…”
Section: Discussionmentioning
confidence: 99%
“…the primary azurophilic granules of neutrophils, into the extracellular compartment. CD is located in fibroblasts and macrophages of the subepithelial connective tissue and in desquamating junctional epithelial cells of the gingival crevice (Ayasaka et al 1993). Under lower acidic conditions (pH 3–7), the release of CD, which is inhibited by pepstatin, induces the activation of a variety of enzymes that contribute to the tissue degradation process (Buchmann et al 1994).…”
mentioning
confidence: 99%
“…Lysosomal cysteine and aspartic acid proteinases have been detected in several epithelial tissues. Cathepsin D has been detected in the coronal portion of rat junctional epithelium (9). By immunohistological methods cathepsins B, C, D, H, and L have been detected in urinary bladder epithelium (182).…”
Section: Epithelial Cell Proteinasesmentioning
confidence: 99%